Survey of practices around pharmaceutical company funding for continuing professional development among medical oncologists and trainees in Australia. Issue 8 (August 2017) - Lee, Yeh Chen; Kroon, René; Koczwara, Bogda; Haines, Ian; Francis, Kay; Millward, Michael; Kefford, Richard; Olver, Ian; Mileshkin, Linda
Abstract: Background: The completion of continuing professional development (CPD) is mandatory for medical oncologists and trainees (MO&T). Pharmaceutical companies may fund some CPD activities, but there is increasing debate about the potential for conflicts of interest (COI). Aim: To assess current practices around funding to attend CPD activities. Methods: An electronic survey was distributed to Australian MO&T. The survey asked questions about current practices, institutional policies and perceptions about attending CPD funded by pharmaceutical companies. The design looked at comparing responses between MO&T as well as their understanding of and training around institutional and ethical process. Results: A total of 157 of 653 (24%) responses was received, the majority from MO (76%). Most CPD activities attended by MO&T were self‐funded (53%), followed by funding from institutions (19%), pharmaceutical companies (16%) and salary award (16%). Most institutions allowed MO&T to receive CPD funding from professional organisations (104/157, 66%) or pharmaceutical companies (90/157, 57%). A minority of respondents (13/157, 8%) reported that the process to use pharmaceutical funds had been considered by an ethics committee. Although 103/157 (66%) had received pharmaceutical funding for CPD, most (109/157, 69%) reported never receiving training about potential COI. The lack of education was more noticeable among trainees (odds ratio (OR) 8.61, P = 0.02). MO&T acknowledged the potential bias towards a pharmaceutical product ( P = 0.05) but believed there was adequate separation between themselves and pharmaceutical companies ( P < 0.01). Conclusion: Majority of CPD attended by MO&T is self‐funded. There is lack of clarity in institutional policies regarding external funding support for CPD activities. Formal education about potential COI is lacking.